Calibration and Validation of Condition Indicator for Managing Urban Pavement Networks. Issue 1 (January 2014) - Osorio, Alelí; Chamorro, Alondra; Tighe, Susan; Videla, Carlos
Deterioration indexes that may combine types of surface distresses, serviceability, and structural indicators are commonly used for pavement management at the network level. These indexes differ in the types of deterioration and criteria considered to quantify severity and density of distresses. Most of these indexes were developed for interurban road networks; therefore, their application to urban networks is complex and not representative. For this reason, there is a need for a better understanding of urban pavement behavior to enable collection of the distresses relevant to these types of pavements and development of an overall condition index for urban pavements that represents the mix of the more relevant distresses for use in network analysis. This study is part of a 3-year project developed in Chile: Research and Development of Solutions for Urban Pavement Management in Chile. The main objective of this study was to calibrate and to validate an urban pavement condition index (UPCI) representative of the overall condition of these pavements, according to objective measures of surface distresses and evaluations of an expert panel. The scope of this study included the development of distress evaluation guidelines for asphalt and concrete pavements considering manual and automated surveys, the application of these guidelines in different types of urban networks, and the assessment of these networks by an expert panel. Finally, three UPCI equations were obtained with satisfactory validation for asphalt pavements with manual and automated data collection and for concrete pavements with manual data collection.